View of the Kalika Devi Temple - Temples of India Project Team (Jio Institute, 2024)
Near the north entrance of the Chandrabhaga temple complex is a flat-roofed structure known as the Kalika Devi Temple. It is commonly referred to as the Navadurga shrine. The temple has an antarala (vestibule or antechamber) and a garbhagriha (sanctum sanctorum). Currently, it is used as the storehouse for the site by the Archaeological Survey of India.